The impact of bank regulation and supervision on banking performance following the global financial crisis - SI, ZIYU (2016)
This paper introduces the latest and updated information of the Bank Regulation and Supervision Survey (BRSS) investigated by the World Bank in 2011-2012, and mainly evaluate two questions. First of all, as for theoretical part, we learn the knowledge of bank regulation and supervision and compare the difference as well as similarities among different versions of BRSS published in 2001, 2003, 2007 and 2012 respectively. And then theoretically analyze the bank regulation and bank supervision among various of countries over the world. In addition, when empirical part taken into account, we learn the former analysis and methodology in terms of impact of bank regulation and supervision on banking performance on the basis of cross country dataset, and establish the similar measurement model to test the relationship between bank regulation and supervision and the level of banking development over 40 counries, using the current available relevant data from Bankscope and collecting bank regulation and supervision data from BRSS as well.